Evaluation of the Productive Behavior and Quality of Different Varieties of Strawberries (Fragaria x ananassa) Cultivated in Santiago del Estero, Argentina - Ruiz, Silvana Cecilia (2026)
Artículo presentado al 6th International Electronic Conference on Foods, 28–30 October 2025